(untitled) - Partha Dasgupta (Massachusetts, 1982)
The book develops several aspects of the theory of resource utilization to a greater depth and with greater subtlely than any other treatise
Keywords: environmental policy,fishery resources,human ecology,water, underground,welfare economics